Structural composition of phytoplankton communities in the tropical Thamirabarani estuary, Southeast coast of India - Srinivasan, V.; Senthil Kumar, D.; Manokaran, S. (Current Botany, 2025)
This study investigated the seasonal effects on phytoplankton populations in the Thamirabarani estuary on India’s southeast coast. 49 species from 31 genera, 24 families, and three phyla (bacillariophyte, miozoa, and cyanobacteria) were identified. The number of species, density, and Margalef richness (d’) were high in the pre-monsoon season (43±1 cells/L, 8463±72 ind./m3, 4.64±0.12 ind./m3) and low in the post-monsoon season (35±1 cells/L, 6448±262 ind./m3, 3.84±0.10 ind./m3) with significant serial changes (ɤ-0.43) in species composition between the seasons. However, these parameters did not show any significant variations in station-wise. The phytoplankton relationship with environmental factors (especially temperature, pH, phosphate, ammonia, salinity, silicate, and chloride) indicated the influence of the nutrient dynamics on plankton communities due to anthropogenic discharges and vegetations (agricultural land and mangroves) in the study area. Hence, suitable improvement strategies have been implemented in this area, and its computation demonstrates the link between phytoplankton abundance and the most effective environmental parameters.